Planning a Clinical Development Programme for Medicinal Products for Irritable Bowel Syndrome: An Analysis of the European Medicines Agency’s Recommendations - E. A. Gerasimets; N. A. Rumyantsev; R. S. Ilin; D. V. Goryachev (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Irritable bowel syndrome (IBS) is a chronic functional disorder present in over 13% of the population. Despite the wide prevalence of IBS, there is currently a lack of well characterised authorised medicinal products to treat IBS. This situation stems from both poor engagement in the development of such medicinal products and the absence of sound approaches to their regulatory review. The intensification of drug development aimed at improving the safety and efficacy of IBS therapy in the context of the growing common pharmaceutical market of the Eurasian Economic Union (EAEU) requires guidelines for planning and conducting clinical trials of medicinal products for IBS.AIM. This study aimed to evaluate the possibility of using the methodological approaches described in international guidelines for the development of national recommendations for conducting clinical trials of medicinal products for IBS.DISCUSSION. The authors analysed the main provisions of the Guideline on the evaluation of medicinal products for the treatment of IBS by the European Medicines Agency (EMA). The analysis identified the methodological tools, the scope and stages of clinical trials, and the efficacy criteria for each study stage. The authors assessed the specific aspects of diagnosing IBS, which are considered when determining the effectiveness of therapeutic interventions. This review highlighted the need for the harmonisation of national and international methodological approaches to the evaluation of clinical trial results that would ensure more robust results of clinical trial reviews conducted in different countries. The authors determined the considerations for planning exploratory and confirmatory clinical trials, including the selection of endpoints, design, and duration of clinical trials in adults and children, as well as the sex distribution of the trial population.CONCLUSIONS. The EMA’s recommendations may guide the planning of clinical programmes for novel medicinal products for IBS. These recommendations may be applied by experts reviewing clinical trial results, as well as developers creating new medicinal products.